Conformational & spectroscopic characterization, charge analysis and molecular docking profiles of chromone-3-carboxylic acid using a quantum hybrid computational method. Issue 10 (October 2020) - Jayasheela, K.; Nagabalasubramanian, P.B.; Periandy, S.
Abstract: The Spectroscopic profile of Chromone-3-Carboxylic Acid (abbreviated as C3CA) was examined using FT-IR, FT-Raman, UV, 1 H and 13 C NMR techniques. The geometrical parameters and energies attained from DFT/B3LYP method with 6–311++G (d, p) basis sets calculations. The geometry of the molecule was fully optimized, vibrational spectra were calculated and assigned the fundamental vibrations on the basis of the total energy distribution (TED) of the vibrational modes, calculated with scaled quantum mechanics (SQM) method. The XRD data obtained from the computed geometric parameters shows that there is little deviation in the structure due to the substitution of the COOH group in the molecule. Using NBO study, the delocalization of the electron and the corresponding attraction between the orbitals shows that the lone pair transition has higher stabilization energy when compared with remaining atoms. The 1 H and 13 C NMR chemical shifts are calculated using GIAO method and the experimental chemical shifts were analysed with theoretical values which reflects better coincidence. The electronic properties, HOMO and LUMO energies, are performed with TD-DFT reproduces good with the experimental findings. Besides, frontier molecular orbitals (FMO), the high reactive nature of the molecule is identified with MEP and global reactivity descriptor analysis are performed. In addition, the molecular docking study was conducted, and results of the docking study identified the sugar phosphatase inhibitor activity of the target molecule (C3CA). Abstract : Materials Science, Materials Chemistry, Theoretical Chemistry, Chromone-3-Carboxylic Acid; DFT; Bacillus subtilis; Hirshfeld surface analysis, charge analysis, electronic properties